2020
DOI: 10.1007/s42452-020-2156-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochar influences nitrogen availability in Andisols of north Idaho forests

Abstract: Biochar application in forest soils can influence tree growth and forest productivity through mediating plant-available nitrogen (N) pools. However, how soil N availability and related transformations respond to biochar addition in cold-temperate forest ecosystems is not well understood. Our study assessed the effect of a hardwood forest residue biochar on soils taken from an elevational gradient within a cold-temperate, north Idaho forest. Forest soils were incubated at 0%, 10% and 20% biochar amendments in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(88 reference statements)
0
0
1
Order By: Relevance
“…Our results showed that 3 years after incorporation, manure, not biochar, increased soil enzyme activities on our coarse-textured sandy loam soil (Figure 2). The lack of a biochar effect is, however, contrary to results observed on fine-textured Andic soil in northern Idaho where biochar altered the activity of several enzymes, including N-acetyl-β-D-glucosaminidase and acid phosphatase (Shan & Coleman, 2020). This difference may be related to soil texture (coarse vs. fine) and suggests that interactions of soil texture, biochar, and manure may be important in understanding enzymatic activity.…”
Section: Discussioncontrasting
confidence: 75%
“…Our results showed that 3 years after incorporation, manure, not biochar, increased soil enzyme activities on our coarse-textured sandy loam soil (Figure 2). The lack of a biochar effect is, however, contrary to results observed on fine-textured Andic soil in northern Idaho where biochar altered the activity of several enzymes, including N-acetyl-β-D-glucosaminidase and acid phosphatase (Shan & Coleman, 2020). This difference may be related to soil texture (coarse vs. fine) and suggests that interactions of soil texture, biochar, and manure may be important in understanding enzymatic activity.…”
Section: Discussioncontrasting
confidence: 75%